Antimicrobial Resistance Profile of Isolates Causing Otitis Externa in Sheltered Dogs (Canis lupus familiaris) - Cunha Del Vechio, Marco Aurélio; Garcia, Matheus Augusto; Kawamo, Denise Miyuki; Brito da Silva, Isadora; Da Silva Oliveira, Halison Murilo; Isabela Carvalho dos Santos; Bianchin Borges, Talita; Dib Gonçalves, Daniela (Acta Scientiae Veterinariae, 2026)
Background: Otitis externa in dogs is one of the most common diseases in veterinary dermatological care, characterized by inflammation of the epithelium of the external auditory canal, increased production of cerumen, itching, and pain. Bacteria and yeasts are often the causative agents. Laboratory diagnosis is essential for accurate identification of the infection. Bacterial multidrug resistance, including the mecA gene, has been described, but few studies have focused on dogs. The aim of this study was to isolate, identify, characterize, and diagnose bacterial resistance in otitis externa of dogs (Canis lupus familiaris) in a municipal shelter in the northwest region of the state of Paraná, Brazil. Materials, Methods & Results:One hundred swab samples were collected from the external auditory canal of 50 dogs (50 females and 50 males, both neutered). The samples were isolated and identified through macroscopic, microscopic, and biochemical tests. The samples were subjected to the disk diffusion test to evaluate antibacterial resistance and molecular identification of Staphylococcus aureus and detection of the mecA gene. Of the 100 samples, 90% (90 samples) showed Gram-positive bacteria, and 10% (10 samples) showed Gram-negative bacilli. Furthermore, 51% of the samples presented Malassezia pachydermatis on cytology. For enterobacteria, the highest prevalence was for Obesumbacterium proteus (3%) and Kluyvera species (2%). In molecular diagnosis, 48% of Staphylococcus aureus isolates were positive for the mecA gene. The highest resistance rate was for Metronidazole (99%), Enrofloxacin (85%), Tetracycline (72%), and Ceftriaxone (42%). Discussion: The results of this study indicate that otitis externa in dogs is frequently associated with bacterial and fungal infections, particularly Staphylococcus aureus and Malassezia pachydermatis. The high antimicrobial resistance observed, especially resistance to Metronidazole (99%), Enrofloxacin (85%), and Tetracycline (72%), and the presence of the mecA gene in Staphylococcus aureus and coagulase-negative Staphylococcus spp., are worrying and indicate an increase in resistance in shelter environments. These findings highlight the importance of accurate diagnosis and the rational use of antibiotics to prevent the development of chronic and antibiotic-resistant infections. The study underscores the importance of rigorous monitoring and more effective treatment protocols to manage antimicrobial resistance in shelter dogs. Keywords: bacteria, One Health, otopathy, veterinary dermatology.